Effects of Creatine Supplementation on Lower-Limb Muscle Endurance Following an Acute Bout of Aerobic Exercise in Young Men - Itamar P. Vieira; Amanda G. de Paula; Paulo Gentil; Claude Pichard; Darren G. Candow; Gustavo D. Pimentel (MDPI AG, 2020)
We aimed to determine whether creatine supplementation influences lower-limb muscle endurance following an acute bout of aerobic exercise (AE) in young healthy men. Using a randomized, double-blind, placebo-controlled crossover design, 11 men (26.5 ± 6.2 years, body mass index 26.6 ± 2.1 kg/m2),with 12 months of experience in strength training (three times/week) and AE (two times/week) were randomized to receive creatine (20 g/day plus 20 g/day maltodextrin) and placebo (40 g/day maltodextrin) for 7 days, separated by a washout period of 14 days, before performing an acute bout of AE (30 min on treadmill at 80% baseline maximum velocity) which was followed by four sets of bilateral leg extension endurance exercise using a 10-repetition maximum protocol (10 RM)). There was a significant decrease in the number of repetitions performed in the third (Placebo: −20% vs. Creatine: −22%) and fourth set (Placebo: −22% vs. Creatine: −28%) compared with the first set (p < 0.05), with no differences between creatine and placebo. Additionally, no differences were observed between creatine and placebo for the total number of repetitions performed across all four sets (Placebo: 33.9 ± 7.0 vs. Creatine: 34.0 ± 6.9 repetitions, p = 0.97), nor for total work volume (Placebo: 3030.5 ± 1068.2 vs. Creatine: 3039.8 ± 1087.7 kg, p = 0.98). Short-term creatine supplementation has no effect on lower-limb muscle endurance following an acute bout of aerobic exercise in trained young men.